Localization effects and pseudogap state in YBa2Cu3O7-d single crystals with different oxygen content: Pseudogap - Obolenskii, M.A.; Vovk, R.V.; Bondarenko, A.V.; Chebotaev, N.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We have investigated the evolution of the temperature dependence of the in-plane and off-plane conductivity of YBa2Cu3O7–d single crystals due to the decrease of the oxygen content in the samples caused by a heat treatment. The concentration dependence of the in-plane and off-plane energy gaps has been determined. It has been shown that the enhancement of the localization effects results in a suppression of the pseudogap state. At the same time, the decrease of theoxygen content results in a relative narrowing of the temperature interval in which the regime of the fluctuating conductivity is realized.